COVID-19 and the Early-Career Physician-Scientist. Fostering Resilience beyond the Pandemic - Kliment, Corrine R. (ATS Sch, 2020)
The coronavirus disease (COVID-19) pandemic has created significant stressors for the academic and scientific community, with unique challenges for early-career physician-scientists. The pandemic-related disruptions have significantly affected research productivity, access to mentoring, professional development and networking opportunities, funding, and personal wellness. This is especially true for pulmonary and critical care medicine faculty because of the burden of specialized clinical care responsibilities that the COVID-19 pandemic has demanded. Departmental, institutional, and national leadership should foster open dialogue to identify and mitigate these challenges to promote ongoing career development of early-career physician-scientists. Implementation of thoughtful interventions to address these challenges will provide essential support for junior faculty and help retain a generation of physician-scientists.